The Effectiveness of Aloe vera Hydrogel Against Fusobacterium nucleatum - Chandra Susanto; Ermi Girsang (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Bacteria can cause infectious diseases on oral health such as gingivitis and periodontitis. Scaling and rootplaning are effective against this disease, nevertheless several types of antimicrobial material can be added to increase the effectiveness of the initial treatment. Aloe vera is one of the natural antimicroba materials that is usually used. Hydrogel is a polymetric material that is stable in wet conditions, especially in the gingival sulcus. Sodium alginate is a natural polymer that is often used to produce hydrogels due to its biocompability. The aim of this study was to know the the effectiveness of Aloe vera hydrogel against Fusobacterium nucleatum by in vitro method. This research is experimental research with a total of 20 samples. The samples used were 5% and 10% sodium alginate based Aloe vera hydrogel which were placed in pure culture of F. nucleatum in MHA media for 24 hours. The inhibition zone diameter were measured using calipers. The results of the study using Shapiro-Wilk normality test showed that the data were not normally distributed. Then Kruskal Wallis test was performed which showed significant differences in each treatment group followed by Post Hoc Mann Whitney test to see a significant difference in the 5% group and 10%. Aloe vera hydrogel showed a significant inhibition against F. nucleatum bacteria at both 5% and 10% concentrations.Keywords: Alginate, Aloe vera, Antimicrobial material, Fusobacterium nucleatum, Hydrogel, Inhibitory zone